Seropositivity of Dengue Antibodies during Pregnancy - Nor Azlin Mohamed Ismail; Wan Elly Rushima Wan Abd Rahim; Sharifah Azura Salleh; Hui-Min Neoh; Rahman Jamal; Muhammad Abdul Jamil (The Scientific World Journal)
Purpose. Malaysia a dengue endemic country with dengue infections in pregnancy on the rise. The present study was aimed at determining dengue seroprevalence (IgG or IgM) during pregnancy and its neonatal transmission in dengue seropositive women. Methods. Maternal with paired cord blood samples were tested for dengue antibodies (IgG and IgM) using an enzyme-linked immunosorbent assay (ELISA). Maternal age, parity, occupation, ethnic group, and gestational age were recorded. Data on neonatal Apgar score and admissions to the Neonatal Intensive Care Unit (NICU) were analyzed. Results. Out of 358 women recruited, about 128 (35.8%) patients were seropositive. Twelve patients (3.4%) had recent infections (IgM positive) and another 116 women (32.4%) were with past infections (IgG positive). All babies born to seropositive mothers had positive IgG paired cord blood; however, no IgM seropositivity was observed. All neonates had good Apgar scores and did not require NICU admission. Conclusion. In this study, 35.8% pregnant women were found to be dengue seropositive. However, transplacental transfer of IgG antibodies had no detrimental effect on the neonatal outcomes.